Perkembangan UMKM Dan Implikasinya Terhadap Potensi Wisata Berbasis Ekonomi Kreatif di Kawasan Desa Wisata - Agung Hirmantono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Tourism is a trip undertaken by individuals or groups to a place temporarily to seek harmony or balance and happiness in the social, cultural, natural and scientific dimensions. Spillane groups the goals of individual/group travel, including enjoying travel, spending time with family, business matters, and others. Tourism development is all forms of coordinated activities with the aim of increasing the number of tourists and improving facilities and infrastructure services, in the form of goods or services and facilities. This is categorized as a complex activity because this activity coordinates activities, facilities and infrastructure, objects and attractions, supporting facilities, environmental facilities and so on with tourists.